2011
DOI: 10.1093/neuonc/nor045
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic high-grade gliomas in children: a distinct clinical subset?

Abstract: Pediatric high-grade gliomas (HGGs) of the thalamic region account for up to 13% of pediatric HGGs and usually result in only anecdotal long-term survival. Because very little is known about these tumors, we aimed to further characterize them. In our series of 99 pediatric thalamic HGGs, there were no significant differences in survival between patients with tumors affecting the thalamus alone (including bithalamic lesions) and patients with tumors affecting the thalamus plus adjacent structures. Tumor resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 17 publications
4
54
0
1
Order By: Relevance
“…14 gliomas (15). Our data showed a genetic molecular correlation that was different between brainstem and thalamic gliomas in adults.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…14 gliomas (15). Our data showed a genetic molecular correlation that was different between brainstem and thalamic gliomas in adults.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…Of these publications, 20 were case series (Table). 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Histologically, the vast majority (70%-90%) of reported thalamic tumors are classified as astrocytoma. However, this literature is limited and difficult to interpret regarding histologic subtypes in children, as many studies combine age groups, are confined to more specific entities (eg, pilocytic astrocytoma (PA) or ''high-grade astrocytoma''), group biologically distinct entities (eg, PA and low-grade diffuse astrocytoma [DA] as ''low-grade astrocytoma''), or are single case reports.…”
Section: Epidemiologymentioning
confidence: 99%
“…12,15,25 However, it is likely that much of the perceived benefit of resection (and possibly grade) is conferred by the significant number of PAs included in most samples as well as the difficulty of distinguishing between PA and low-grade DA in small biopsies. Five-year survival rates for high-grade thalamic DA have tended to average 15% to 25% in the literature, 1,33 although these numbers are quite variable. Moreover, recent studies 13,21 have indicated that extent of resection may not be as prognostically important as originally believed, particularly in high-grade and/or bithalamic DA, which suggests that additional biologic factors related to thalamic location may be influencing outcome.…”
Section: Diffuse Astrocytomamentioning
confidence: 99%
See 2 more Smart Citations